Post-Translational Modifications and Diabetes - Chiranjeev Sharma; Abu Hamza; Emily Boyle; Dickson Donu; Yana Cen (Biomolecules, 2024)
Diabetes and its associated complications have increasingly become major challenges for global healthcare. The current therapeutic strategies involve insulin replacement therapy for type 1 diabetes (T1D) and small-molecule drugs for type 2 diabetes (T2D). Despite these advances, the complex nature of diabetes necessitates innovative clinical interventions for effective treatment and complication prevention. Accumulative evidence suggests that protein post-translational modifications (PTMs), including glycosylation, phosphorylation, acetylation, and SUMOylation, play important roles in diabetes and its pathological consequences. Therefore, the investigation of these PTMs not only sheds important light on the mechanistic regulation of diabetes but also opens new avenues for targeted therapies. Here, we offer a comprehensive overview of the role of several PTMs in diabetes, focusing on the most recent advances in understanding their functions and regulatory mechanisms. Additionally, we summarize the pharmacological interventions targeting PTMs that have advanced into clinical trials for the treatment of diabetes. Current challenges and future perspectives are also provided.